The Influence of Flexible Work Arrangements toward Loyalty and Innovative Work Behavior Mediated by Work-Life Balance - Iis Astriani; Muafi Muafi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
Uncertain situations are very vulnerable for organizations maintaining their activities. Organizations must have a strategy to maintain the availability of human resources. One of the strategies carried out by the organization is to create flexible work arrangements which are predicted to be a solution in the future to increase job satisfaction, commitment, and work-life balance and encourage employees to provide higher performance and innovation. This study used PLS (Partial Least Square) analysis tools and a sample size of 117 respondents. The results showed that flexible work arrangements affect work-life balance, loyalty, and innovative work behavior. Furthermore, work-life balance mediates the relationship of flexible work arrangements towards loyalty as well as mediates the relationship of flexible work arrangements towards innovative work behavior. This study was conducted to determine work flexibility and its relationship towards loyalty and innovative work behavior with the object of research of lecturers at Qamarul Huda Badarrudin University, Central Lombok.